The Dun-Gibson Index Number - Mitchell, Wesley C. (Quarterly Journal of Economics, 1910)
Journal Article The Dun-Gibson Index Number Get access Wesley C. Mitchell Wesley C. Mitchell University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 25, Issue 1, November 1910, Pages 161–172, https://doi.org/10.2307/1885829 Published: 01 November 1910